The Influence of Watching English Cartoons on English Language Acquisition: A Case of Selected Filipino Preschoolers - Trota, Mark Phel Boreres; Cabeltis, Chariebelle Bacatano; Cadiente, Nicole Tamaca; Ligan, Mikee; Asoy, Nicole Marie Caubalejo; Bardaje, Zosimo L. (Universitas Siliwangi, 2022)
In this 21st century era, young children have become keen users of multimedia technologies, more so than in the past generations when children could access various English cartoons. Due to exposure to English cartoons, preschoolers proficient in English tend to have difficulties acquiring the first language used in the speech community. Therefore, the study investigated the influences of English cartoons on preschoolers’ English language acquisition. It is anchored on Skinner’s Behaviorism, Krashen-Terrell’s Input Hypothesis, Kress and Van Leeuwen’s Multimodal Discourse, and Critical Age Period Theory. It adheres to Yin’s single holistic case study research design, where two (2) preschoolers were selected through a purposive sampling technique. The data were gathered during the four-week series of home observations and semi-structured in-depth interviews within the seven-month study duration. Furthermore, data were analyzed following the thematic analysis method. Results revealed that preschoolers’ English language acquisition is affected by certain factors, i.e., exposure to multimedia technologies, social relationship/linguistic environment, motivation, attitudes, and interests of the child. Regarding phonological influence, preschoolers articulate terms based on the pronunciation heard from cartoon shows. F/P1 acquires a British accent, and both participants can utter all vowel/consonant sounds except ‘r.’ They can use words even without understanding their context. Concerning semantic influence, active exposure to cartoons and engagement in an immediate environment led to meaning-making processes strengthening critical and creative thinking skills. Regarding syntax, participants’ multi-word utterances are drawn from longer potential sentences that express a complete thought. Although the words produced are ungrammatical by adults’ standards, they still adhere to grammatical rules. Keywords: English Language Acquisition; English Cartoons; Preschoolers; Factors; and Influence.